A voice for Eurydice: approaching the Orpheus myth from a feminist perpective - Yalınateş Bilgen, Hande. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This study argues that the Orpheus myth is originally a transition between goddess cultures and patriarchal religions by revealing the in betweenness of the myth and to what purpose it serves through the works of Ovid’s Metamorphoses (Book X, Fable I-II; Book XI, Fable I) (8 AD), Rainer Maria Rilke’s poem “Orpheus. Eurydice. Hermes” (Neue Gedichte) (1904), Kathy Acker’s play Eurydice in the Underworld (1997) and Sarah Ruhl’s play Eurydice (2003) which all use the Orpheus myth as their basis. This thesis also attempts to scrutinize the dual nature of the myth between Apollo-representing patriarchy and Dionysus-bearing characteristics of matrilineality. In this respect, this study extensively borrows from feminist theories of matrilineality which, it is assumed, respect the female and the concepts related to her yet do not degrade the male and the notions associated with him.
Keywords: Eurydice (Greek mythology) in literature.; Orpheus (Greek mythology) in literature.